การพัฒนารูปแบบการจัดการความรู้การบริหารยาที่ต้องระมัดระวังสูงของหัวหน้าหอผู้ป่วยโรงพยาบาลสังกัดกองทัพบก A Development of Knowledge Management Model of High Alert Drug Administration for Head Nurses in Hospitals Under Royal Thai Army - โภคศิริ มลฤดี; ภักดีวงศ์ ภาณุวัฒน์; วรรณพรศิริ ชมนาด (Journal of The Royal Thai Army Nurses, 2014)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนารูปแบบการจัดการความรู้การบริหารยาที่ต้องระมัดระวังสูงของหัวหน้าหอผู้ป่วยโรงพยาบาลสังกัดกองทัพบก การดำเนินการวิจัย ศึกษาสภาพปัญหาและความต้องการด้วยการสังเคราะห์แนวคิด ทฤษฎี งานวิจัยที่เกี่ยวข้อง และสัมภาษณ์ หัวหน้าหอผู้ป่วยโรงพยาบาล 3 กลุ่ม เลือกแบบเฉพาะเจาะจงจำนวน 36 คน เพื่อนำมาร่างรูปแบบ และตรวจสอบคุณภาพของรูปแบบโดยผู้เชี่ยวชาญจำนวน 9 คน และนำไปทดสอบประสิทธิผลของรูปแบบด้วยการทดลองใช้และประเมินรูปแบบโดยหัวหน้าหอผู้ป่วย โรงพยาบาลค่ายสมเด็จพระนเรศวรมหาราช จำนวน 9 คน การวิเคราะห์ข้อมูล ข้อมูลเชิงคุณภาพ วิเคราะห์ด้วยการวิเคราะห์เนื้อหาและข้อมูลเชิงปริมาณ วิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และค่าสถิติ t-test ผลการวิจัยพบว่า รูปแบบการจัดการความรู้การบริหารยาที่ต้องระมัดระวังสูงของหัวหน้าหอผู้ป่วยได้รูปแบบที่เรียกย่อว่า “SIMPLE” ซึ่งมี 6 องค์ประกอบ และผลการทดสอบประสิทธิผลของรูปแบบการจัดการความรู้การบริหารยาที่ต้องระมัดระวังสูงของหัวหน้าหอผู้ป่วยพบว่า ค่าเฉลี่ยความรู้และระดับการปฏิบัติหลังใช้รูปแบบสูงกว่าก่อนใช้รูปแบบอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และมีความพึงพอใจมาก The research aimed to Develop a knowledge management model of high alert drug administration for head nurses in hospitals under Royal Thai Army. Method: Research data had been drawn from documentary studies, Thirty six key informants from head nurses of three hospital groups were selected by using purposive sampling technique. Qualitative data were collected through interviews that used for develop a model. A draft of model was examined by nine experts, to evaluate effectiveness of knowledge management model of high alert drug by using a quasi-experimental design, The experimental group consisted of nine head nurses in Fort Somdet Pranaresuan Maharat Army hospital. Analysis: Qualitative data was analyzed by content analysis, and quantitative data was analyzed to the arithmetic mean, standard deviation and t-test. Results: The model of knowledge management of high alert drug administration for head nurses was abbreviated as SIMPLE Model which consisted six components, and the experiment of drafted model revealed that average scores from pre-tests and post-tests of knowledge and practice levels showed a significant difference at the .05 level, and satisfaction was in high level. Conclusions: The study results would be the guideline for head nurses developed knowledge management for high alert drug administration efficient systems.